Peran Pembelajaran Berbasis CAD terhadap Penguasaan Kompetensi Gambar Teknik di Pendidikan Vokasi: Tinjauan Literatur (2021–2025) - Arisman Telaumbanua; Rena Ria Zalukhu (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Digital transformation and increasing industry demands have urged vocational education to strengthen technical drawing competencies through Computer-Aided Design (CAD)–based learning. This article reviews literature published between 2021 and 2025 to map the contributions of CAD-based instruction to the mastery of technical drawing competencies, effective pedagogical strategies, assessment approaches, and enabling and constraining factors influencing its implementation in vocational education settings. The review employed a structured literature review approach and was reported in accordance with PRISMA 2020 principles to ensure transparency and replicability. A total of 32 studies that met the inclusion criteria were synthesized thematically. The findings indicate that CAD-based learning plays a significant role in: (1) improving drawing accuracy, standard consistency, and drafting productivity through 2D/3D visualization and efficient revision processes; (2) strengthening spatial visualization skills and projection understanding through the integration of CAD with orthographic projection principles and the support of augmented reality (AR) technologies; (3) enhancing students’ work readiness by aligning learning activities with CAD/BIM-based industrial workflows and digital documentation practices; (4) increasing learner engagement and motivation when combined with project-based learning, problem-based learning, case methods, and interactive multimedia; and (5) requiring adequate teacher competencies, access to hardware and software licenses, and instructional designs that effectively manage learners’ cognitive load. This article proposes a vocational CAD learning implementation framework that integrates competency-oriented objectives, industry-based authentic tasks, cognitive load scaffolding, and performance-based assessment rubrics as a reference for developing technical drawing instruction in vocational education.